GAMBARAN PENGETAHUAN IBU HAMIL TRIMESTER I TENTANG EMESIS GRAVIDARUM - Farida Utaminingtyas; Lola Pebrianthy (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2020)
Backgroud: Nausea and vomiting (emesis gravidarum) are symptoms that often occur in 60-80% Primigravida and 40-60% Multigravida. The causes of nausea and vomiting vary, among others, due to hormonal changes in the body, psychological, to lifestyle. The purpose of this study was to determine the description of knowledge of trimester 1 pregnant women about emesis gravidarum. Methods: This research design uses descriptive research type. The sample of this study was the first semester pregnant women who came to have their pregnancy examined at the Rasoki Labuhan Public Health Center in August 2018, amounting to 30 people. The sampling technique uses accidental sampling. The research instrument was in the form of questionnaire sheets and mother's MCH handbook. Results: Data processing techniques starts from editing, coding, tabulation and finally data analysis. From the total of 30 respondents, 7 (23.3%) data have good knowledge, 16 (53.4%) respondents have sufficient knowledge and 7 (23.3%) respondents who have less knowledge about emesis gravidarum. It is expected that first trimester pregnant women will seek more complete information on emesis gravidarum.